Data use aids adaptation and continuation of maternal, infant and young child nutrition (MIYCN) services in urban health facilities in Bangladesh during the COVID-19 pandemic - Escobar-DeMarco, Jessica; Ireen, Santhia; Kabir, Rowshan; Kundu, Gourob; Asaduzzaman, H. M.; Jahan, Rezwana; Nguyen, Phuong Hong; Ash, Deborah (International Society for Human and Animal Mycology, 2022)
The COVID-19 pandemic disrupted health services worldwide. Alive and Thrive (A&T) is testing MIYCN integration into non-governmental organizations’ (NGOs) health services in eight facilities in Dhaka. We aimed to develop a data-driven urban MIYCN intervention pathway adapted to continue delivering nutrition services during COVID-19.